The Darling Dahlias and the naked ladies [large type] - Albert, Susan Wittig (Albert, Susan Wittig. Darling Dahlias mysteries., 2011)
Rumors are sprouting in Depression-era Darling, Alabama. The town's newest visitors, Nona Jean Jamison and Miss Lake, may be the Naughty and Nice Sisters from the Ziegfeld Frolic, who specialize in dancing nearly naked. The Dahlias suspect more than modesty when Nona denies her association.